2006
DOI: 10.1002/acp.1316
|View full text |Cite
|
Sign up to set email alerts
|

I'll keep you in mind: the intimacy function of autobiographical memory

Abstract: An experimental study examined whether autobiographical memory serves the function of maintaining intimacy in romantic relationships. Young and older adults (N ¼ 129) recalled either autobiographical relationship events or fictional relationship vignettes. Intimacy (warmth, closeness) was measured before and after remembering. Warmth was enhanced after recalling autobiographical events irrespective of individuals' age and gender; women also experienced gains in closeness. The role of memory characteristics (qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
205
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(224 citation statements)
references
References 55 publications
11
205
0
4
Order By: Relevance
“…From this perspective, people who engage in this type of remembering in social contexts may also benefit in an interpersonal sense, although this is more speculative (Alea & Bluck, 2006).…”
Section: Is the Creation Of Self-event Connections Adaptive?mentioning
confidence: 99%
“…From this perspective, people who engage in this type of remembering in social contexts may also benefit in an interpersonal sense, although this is more speculative (Alea & Bluck, 2006).…”
Section: Is the Creation Of Self-event Connections Adaptive?mentioning
confidence: 99%
“…The social function has often been described as the sharing of one's personal memories with others in order to facilitate social bonding, elicit empathy or intimacy, teach, communicate or inform (e.g., Alea & Bluck, 2003;Nelson, 1993;Pillemer, 1992), but may also involve memories about loved ones, which are not necessarily shared with others (e.g., Alea & Bluck, 2007;Kulkofsky, Wang & Hou, 2010). The three functions have been examined in relation to concrete memories (e.g., Alea & Bluck, 2007;Hyman & Faries, 1992;Kulkofsky et al, 2010;Mclean & Lilgendahl, 2008;Pasupathi, Lucas and Combs, 2002;Rasmussen & Berntsen, 2009a; as well as in survey studies addressing people's overall usage of the three functions generalized across concrete memories (e.g., Bluck, Alea, Habermas & Rubin, 2005, Cappeliez & O'Rourke, 2002Cappeliez, O'Rourke & Chaudbury, 2005;Webster, 1993;1997). Here, we focus on the latter.…”
mentioning
confidence: 99%
“…Although some researchers have suggested that memories may also serve intimacy functions-even if they are not shared with others (Alea & Bluck, 2003, 2007b)-we define social memories as memories that are often shared. We choose this definition because memory sharing is theorized to be one of the primary functions of autobiographical memory (e.g., Nelson, 1993), and because this definition minimizes conceptual .…”
mentioning
confidence: 99%
“…The social function is apparent when individuals share their memories with others in order to persuade, ease communication, facilitate social bonding, and elicit empathy or intimacy (see, e.g., Alea & Bluck, 2007b;Cohen, 1998;Pillemer, 1992). Although some researchers have suggested that memories may also serve intimacy functions-even if they are not shared with others (Alea & Bluck, 2003, 2007b)-we define social memories as memories that are often shared.…”
mentioning
confidence: 99%